A duplex PCR assay for the simultaneous detection and differentiation of Muscovy duck parvovirus and goose parvovirus. (October 2019) - Wan, Chunhe; Cheng, Longfei; Chen, Cuiteng; Liu, Rongchang; Shi, Shaohua; Fu, Guanghua; Chen, Hongmei; Fu, Qiuling; Huang, Yu
Abstract: Both Muscovy duck parvovirus (MDPV) and goose parvovirus (GPV) can cause high mortality and morbidity in Muscovy ducklings. MDPVs and GPVs share high nucleotide identity, which can cause errors during differential diagnosis. In this study, the NS genes of both MDPVs and GPVs were chosen for the design of specific primers after genetic comparison. Only three primers (GF1, MF1 and MGR1) were designed for the duplex PCR assay: GF1 is specific for GPV only; MF1 is specific for MDPV only; and MGR1 is highly conserved for both MDPV and GPV. After a series of optimization experiments, the duplex PCR assay amplified a 161-bp fragment specifically for GPV, a 1197-bp fragment specifically for MDPV, and two fragments (161-bp and 1197-bp) for both GPV and MDPV. The lowest detection limit was 10 3 copies/μl. No amplification was obtained using nucleic acids from other pathogens (including DAdV-A, DuCV, DEV, GHPV, R.A., E. coli., P.M. and S.S.) occurring in Muscovy ducks. Application of the duplex PCR assay in field samples showed that even one-day-old Muscovy ducklings were both MDPV-positive and GPV-positive. In conclusion, a duplex PCR assay for the simultaneous detection and differentiation of MDPV and GPV was established using only three highly specific primers. Our finding suggested that country-wide vaccination with MDPV and GPV vaccines in waterfowls are necessary. Highlights: We established a duplex PCR assay for the simultaneous detection and differentiation of MDPV and GPV. The established method showed highly sensitivity and specificity. Our finding suggested that country-wide vaccination with MDPV and GPV vaccines in waterfowls are necessary.